Game-Based Learning and Gamification for Education (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The use of educational games and gamification in teaching has been a global trend in educational research, and this reprint focuses on research related to the use of game-based learning or gamification in teaching. This reprint contains empirical studies and systematic reviews regarding the use of games in teaching, spanning many subject areas. It includes various gamification mechanisms, escape room educational games, the evaluation of various digital educational games, and other topics.